Comparative Analyses of Non Enzymatic and Enzymatic Antioxidants of Enicostemma Littorale Blume - R. SATHISHKUMAR; PALANISWAMY THANGA VELAN LAKSHMI; ARUNACHALAM ANNAMALAI (International Journal of Pharma and Bio Sciences, 2010)
The objective of this study was to characterize the non-enzymatice and enzymatic antioxidants of E. littorale Blume grown under wild condition. Aerial and sub-aerial parts of the plants exposed to different heat stress was analyzed for the non enzymatic antioxidants such as Tocopherol, Phenols, DPPH, FRAP and enzymatic antioxidants such as Polyphenol oxidase, Peroxidase, Catalase, Super Oxide Dismutase, which revealed quite an interesting observation. In the plant, the enzymatic antioxidant activity was found to be significant in the shade dried extracts. This enzymatic antioxidant activity concludes the potential degradation of free radicals. The non-enzymatic antioxidant activity contributes significantly in both fresh and shade dried extracts except the DPPH activity which found to be significant in the sun dried extracts of the plant material.